Aspectos clínicos e comportamento dos marcadores bioquímicos da síndrome metabólica no pós-operatório tardio do transplante hepático - Lucilene Rezende Anastacio (2014)
Background: Metabolic syndrome (MS) has been widely reported among liver graft recipients on the early years after liver transplantation (LTx), however, there are few studies of this condition in the long-term. Furthermore and despite the amount of data on the role of adipokines under this condition, there is scarce information after LTx. Objetivos: To longitudinally describe the prevalence of MS, its components and associated factors in long-term LTx survivors. In a subgroup of individuals, we have studied the pathophysiological mechanisms by means of serum adipokines, inflammatory and insulin resistance markers. Methods: This was a longitudinal study in which 117 patients were evaluated in two distinct times (2008 e 2012) for the presence of MS (National Cholesterol Education Program Adult Treatment Panel III revised NCEP ATP III, International Diabetes Federation - IDF e Harmonizing the Metabolic Syndrome HMS criteria) and its components, as well as body composition parameters and dietary intake. Demographic, socioeconomic and clinical data were also collected. In 34 patients, serum dosages of adiponectin, resistin, Tumor Necrose Factor (TNF-a), monocyte chemoattractant protein-1 (MCP-1), interleukin-6 (IL-6), (MCP-1), free fatty acids (FFA), C-protein reactive (CPR), fasting insulin and blood glucose for HOMA-IR (Homeostatic Model Assessment) calculation were transversally assessed. Potential associated factors with MS and its components were assessed using multivariate logistic regression. Potential associated factors to adipokines, inflammatory and insulin resistance markers were studied using multiple linear regression. Results: MS was diagnosed in 43.1% (IDF/HMS) and 34.3% (NCEP) in patients who underwent LTx with median follow-up of 3 years (range 0-13 years) and these numbers were 53.3% (p=0.12) and 44.8% (p=0.03), respectively, when patients had median of 7 years of follow-up (range 3-17 years) (p=0.12 e p<0.01, respectively). The prevalence of hyperglycemia increased from 34.2% to 48.6% (p<0.01). The waist circumference rose from 93.314.3cm to 99.414.9cm (p<0.01) and body fat percentage from 30.38.9% to 31.810.3% (p=0.03). Abdominal obesity prevalence by the IDF/HMS criteria increased from 66.7% to 72.0% (p=0.09). Associated factors to MS were: older age (OR: 1.05; CI: 1.02-1.11; p=0.02), familiar history of diabetes (OR: 3.38; CI: 1.19-9.61; p=0.02), greater body mass index (BMI) prior to liver disease (OR: 1.39; CI: 1.19- 1.63; p<0.01) and body fat percentage (OR: 1.09; CI: 1.03-1.14). MS components (abdominal obesity, arterial hypertension, hyperglycemia) were associated to older age (p<0.05). Abdominal obesity was associated to greater body fat amount (p=0.01) and lack of exercise (p=0.01). Low HDL was associated to increased BMI (p<0.01), greater fat (p=0.03) and carbohydrate intake (p=0.03). High triglycerides were associated to current corticosteroid use (p=0.04), family history of diabetess (p=0.04), greater BMI (p<0.01) and increased fat intake (p<0.01). Higher adiponectin concentrations (6.74.5 g/mL versus 3.21.2 g/mL. p<0.01) and FFA concentrations (0.80.3 mEq/L versus 0.50.3 mEq/L. p<0.05) and greater HOMA-IR values (4.93.8 versus 1.60.8) were observed in LTx receptors diagnosed with MS. Increased waisthip ratio and low HDL were independent of adiponectin concentrations (p<0.05). Lower resistin concentrations were seen in patients with high blood pressure and greater, in those with abdominal obesity (p<0.05). HOMA-IR values were independently predicted by obesity and MS (p<0.05). Independent variables associated to TNF-a, MCP-1, IL-6 and FFA were not identified. Conclusion: MS was observed in more than half of the liver graft recipients on the long-term. There was an increase in the prevalence of MS over the years, as well as for the waist circumference and blood glucose. MS and its components were associated to potentially modifiable factors, as greater BMI and body fat, lack of exercises, current use of corticosteroids and increased intake of fat and car bohydrates. MS and its components were associated with FFA, as well as with HOMA-IR, increasing both of them. Adiponectin, resistin and other inflammatory markers (TNF, IL-6, MCP-1 and CRP) did not portray the MS in this sample of patients who underwent LTx.